The impact of relaxation in prenatal yoga against the anxiety level in pregnant women - Nendhi Wahyunia Utami; Dewi Zolekhah (Alma Ata University Press, 2021)
Background: The anxiety and stress level impact the outcome of labor such as premature baby, LBW, infant abnormality, and infection. Prenatal Yoga is one of the complementary therapies given to pregnant women so that able to give well-being and serenity to the pregnant women and able to decrease the anxiety level at the time of labor.Objectives: To understand the impact of relaxation in prenatal yoga against the anxiety level in pregnant women.Methods: This research is conducted with quasi-experimental pre-and post-test method with cross sectional approach. The sample is 3rd trimester pregnant women as amount as 16 respondents each group with purposive sampling technique. The treatment is given Yoga Breathing intervention and control according to the standard of care, both groups’ anxiety levels are measured before and after the intervention using HARS. Student t test is used to determine whether there is a difference between the treatment group and the control group in the results of anxiety measuring. Analysis of variance is used to compare between 2 groups, whether there is an effect of anxiety on the Chi Square test intervention to determine whether there is a difference in the 2 treatment and control groups.Results: The results of the analysis using the chi-square showed that p <0.001 RR Score = 5.64 at 95% CI 1.99-15.93, which means that prenatal yoga treatment has a significant effect on decreasing the anxiety in pregnant women (p <0.05). Based on the bivariate analysis, it shows that prenatal yoga classes have a significant effect on reducing anxiety in pregnant women by 5.64 times compared to conventional methods.Conclusion: the level of anxiety of pregnant women in facing the first labor by following relaxation in pregnatal yoga before and after treatment is moderate, decreases to mild.